(untitled) (Research, Society and Development, 2021)
The nurse has a key role in the implementation of care practices that enhance the management of diabetes mellitus by the patient in the hospital. It aims to describe the nurses’ care practices given to people with diabetes mellitus during hospitalization. This is a qualitative research carried out in a teaching hospital in the southern region of Brazil. Fieldwork was carried out from September to October 2019, among 15 nurses from clinical, medical and urgent and emergency units selected through an intentional sample. The data production technique included semi-structured interviews and the Ethnograph V6 Program was used to organize and manage the data, which were analyzed through content analysis. Three categories were constructed: the first, Nursing Care Systematization, which the importance of its development was consciously recognized, highlighted the nursing prescription as essential to provide care practices; the second, Assistance Activities is about the control and monitoring of capillary glycemia, management of insulin application, monitoring of acute episodes of hypoglycemia or hyperglycemia and, the third, Educational Activities refers to individual and collective guidelines that correspond to food, use of medicines, foot care and (re) knowing the changes that occur in the body itself. The practices developed aim at both the recovery and promotion of health and the prevention of complications in the perspective of promoting the self-care of people with diabetes and their preparation to return to their homes.